The Comparison of Gabapentin and Amitriptilin Effectivity as Pain Therapy in Herniated Nucleus Pulposus - Indriastuti Cahyaningsih; Rina Handayani; Setyaningsih Setyaningsih (Intelektual Pustaka Media Utama, 2015)
Herniated nucleus pulposus (HNP) is one of peripheral neuropathic pain. Although concensus guidelines for the treatment of neuropathic pain are based on the results of the RCT studies, there are still gaps in the literatures. This study aimed to compare the effectiveness and quality of life of gabapentin and amitriptyline for the treatment of pain in HNP. The method used a quasi experimental with consequtive sampling. This study included 30 patients in the gabapentin group and 26 patients in the amitriptyline group, and each group was evaluated for 1 month. Effectiveness was assessed using Visual Analogue Scale (VAS) every 2 weeks then analized by independent and paired sample t test. The results showed that the use of gabapentin and amitriptilin in 4 weeks showed the decrease of pain score measured by visual analog scale 3.70 ± 0.349 and 3.500 ± 0.34 although there was no statistical difference (p value = 0.704). To sum up, effectiveness of gabapentin and amitriptyline in the treatment of neuropathic pain did not have statistical difference.